EEG correlates of seizure freedom in genetic generalized epilepsies. Issue 1 (February 2017) - Seneviratne, Udaya; Boston, Ray C.; Cook, Mark; D'Souza, Wendyl
Abstract: Background: We investigated the association between epileptiform EEG abnormalities and the preceding duration of seizure freedom in genetic generalized epilepsies (GGE). Methods: We analyzed 24-hour ambulatory EEG recordings of patients with GGE diagnosed and classified according to the International League Against Epilepsy criteria. We quantified epileptiform EEG abnormalities into density scores (total duration of epileptiform discharges per hour) and estimated the preceding seizure-free duration at the time of EEG recording based on the last self-reported seizure. We then employed regression analysis to quantitate the relationship between the duration of seizure freedom and EEG variables. Results: We analyzed 6, 923 epileptiform discharges from 105 patients with abnormal 24-hour EEGs. In the regression analysis exploring the crude associations, we found significant correlations between 6 EEG variables and the duration of seizure freedom indicating that shorter duration of seizure freedom was associated with higher spike densities and longer paroxysms. These associations were not affected by confounders such as syndrome, age at EEG, age at epilepsy onset, sex, duration of epilepsy, or number of antiepileptic drugs. Conclusions: Higher densities and longer durations of epileptiform discharges may be retrospectively associated with a shorter duration of self-reported seizure freedom. Hence, EEG can potentially be used as a biomarker of prognosis in GGE. These findings need to be validated in a prospective study in order to define EEG markers of future seizure freedom.